Reacquisition of nef-mediated tetherin antagonism in a single in vivo passage of HIV-1 through its original chimpanzee host - Götz, Nicola; Fritz, Joëlle; Fackler, Oliver Till (Cell host and microbe, 2012)
Summary. The interferon-induced host restriction factor tetherin poses a barrier for SIV transmission from primates to humans. After cross-species transmission, the chimpanzee precursor of pandemic HIV-1 switched from the accessory protein Nef to Vpu to effectively counteract human tetherin. As we report here, the experimental reintroduction of HIV-1 into its original chimpanzee host resulted in a virus that can use both Vpu and Nef to antagonize chimpanzee tetherin. Functional analyses demonstrated that alterations in and near the highly conserved ExxxLL motif in the C-terminal loop of Nef were critical for the reacquisition of antitetherin activity. Strikingly, just two amino acid changes allowed HIV-1 Nef to counteract chimpanzee tetherin and promote virus release. Our data demonstrate that primate lentiviruses can reacquire lost accessory gene functions during a single in vivo passage and suggest that other functional constraints keep Nef ready to regain antitetherin activity.
Available online 12 September 2012
Gesehen am 06.12.2018